2020
DOI: 10.1016/j.healthplace.2019.102278
|View full text |Cite
|
Sign up to set email alerts
|

Associations among neighborhood poverty, perceived neighborhood environment, and depressed mood are mediated by physical activity, perceived individual control, and loneliness

Abstract: Few studies have documented the pathways through which individual level variables mediate the effects of neighborhoods on health. This study used structural equation modeling to examine if neighborhood characteristics are associated with depressive symptoms, and if so, what factors mediated these relationships. Crosssectional data came from a sample of mostly rural, older adults in North Carolina (n ¼ 1,558). Mediation analysis indicated that associations among neighborhood characteristics and depressive sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 80 publications
4
34
0
Order By: Relevance
“…A few recent studies have examined physical activity in combination with social factors as mediators of associations between greenspace and mental health. Loneliness [ 20 , 51 ], and social cohesion [ 28 , 29 , 51 ] were significant, and in some cases stronger mediators than physical activity of the associations between neighborhood resources for physical activity (greenspace and streetscape greenery) and wellbeing and depressive symptoms outcomes. One study did not demonstrate significant indirect associations between residential proximity to neighborhood greenspace and mental wellbeing via leisure-time physical activity, social cohesion, nor perceived stress; however, neighborhood satisfaction significantly mediated the association [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few recent studies have examined physical activity in combination with social factors as mediators of associations between greenspace and mental health. Loneliness [ 20 , 51 ], and social cohesion [ 28 , 29 , 51 ] were significant, and in some cases stronger mediators than physical activity of the associations between neighborhood resources for physical activity (greenspace and streetscape greenery) and wellbeing and depressive symptoms outcomes. One study did not demonstrate significant indirect associations between residential proximity to neighborhood greenspace and mental wellbeing via leisure-time physical activity, social cohesion, nor perceived stress; however, neighborhood satisfaction significantly mediated the association [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The associations between urban parks and mental health are likely due to a variety of factors, including connection to nature and opportunities for social interaction and physical activity. Indeed, studies suggest that social interaction in parks may increase feelings of social support and reduce feelings of loneliness [ 19 , 20 ]. Further, studies examining park attributes have shown that parks with a nature focus and opportunities for recreational activity are associated with positive mental health [ 21 ], while access to large green spaces may encourage physical activity participation [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, access to green spaces and proximity to parks are linked to positive health outcomes for urban residents, including reduced risk of cardiovascular disease and diabetes and less stress (Orstad et al, 2020). Urban parks offer opportunities for improving physical health and contact with nature, which can reduce loneliness and improve psychological well-being (Kowitt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature in and beyond environmental gerontology has provided empirical evidence for the significant role of residential setting or neighborhood environments in older adults' active and healthy aging [1][2][3][4][5][6]. In particular, (neighborhood) environmental correlates of older adults' mental health outcomes and psychological well-being have been greatly examined [7][8][9][10][11][12][13]. These previous studies suggest several pathways of how neighborhood environments may determine older adults' physical health and psychological well-being.…”
Section: Introductionmentioning
confidence: 99%